2019
DOI: 10.1016/j.cegh.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of Mycobacterium tuberculosis lineages on lung tissue damage and TNF-α level among tuberculosis patients, Indonesia

Abstract: Background: Mycobacterium tuberculosis (MTB) is divided into ancient and modern lineage. Both lineages have different virulence property and therefore associated with different immune responses and disease severity in tuberculosis (TB) patients. The aim of this study was to determine the association between MTB lineages and the level of tumor necrosis factor alpha (TNF-α), and lung tissue damage among Indonesian TB patients. Methods: Thirty new and active TB patients were recruited randomly from Dr. Soewandhie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Furthermore, this study showed that hyperemic, edema, ulcerative, and fibrostenosis types were mostly presented in M. tuberculosis strain Beijing than M. bovis strain BCG infection (Table 3). This may be due to differences in virulence between MTBC species and M. tuberculosis Beijing strain has high virulence such as the ability to induce lung parenchymal severe damage with extensive necrotizing pneumonia [30], [31]. An in vitro study showed that there are differences in the ability to induce pulmonary cell death and to release various cellular components as harmful signals in macrophages infected by the M tuberculosis Beijing strain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study showed that hyperemic, edema, ulcerative, and fibrostenosis types were mostly presented in M. tuberculosis strain Beijing than M. bovis strain BCG infection (Table 3). This may be due to differences in virulence between MTBC species and M. tuberculosis Beijing strain has high virulence such as the ability to induce lung parenchymal severe damage with extensive necrotizing pneumonia [30], [31]. An in vitro study showed that there are differences in the ability to induce pulmonary cell death and to release various cellular components as harmful signals in macrophages infected by the M tuberculosis Beijing strain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strongly clonal population structure of the MTBC, evidence is accumulating on phylogenetically associated biomedical consequences of the diversity of the pathogen. This genomic diversity can potentially lead to different pathobiological features, such as disease severity [ 28 , 29 ] and dormancy [ 28 , 30 , 31 ], or can affect treatment outcomes [ 32 ], bacterial fitness [ 33 ], or resistance levels to anti-TB drugs [ 34 ]. (Phylo)genetic determinants of such pathobiological differences have recently been pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of the TbD1 genome region in the more recent lineages (EA, EAI, EuA) is associated with a decrease of immune response level compared to the ancestral lineage (IO) ( Portevin et al., 2011 ). Based on patient serum analysis and macrophage culture experiments, the IO lineage of Mtb induces higher levels of immune activation compared to the EA and EuA lineages ( Amin et al., 2019 ; Portevin et al., 2011 ). Our study using primary cells in culture has also found that immune responses to the IO lineage differ from those to other lineages.…”
Section: Discussionmentioning
confidence: 99%